Cross-ancestry genome-wide meta-analysis of 61,047 cases and 947,237 controls identifies new susceptibility loci contributing to lung cancer - Byun, Jinyoung; Han, Younghun; Li, Yafang; Xia, Jun; Long, Erping; Choi, Jiyeon; Xiao, Xiangjun; Zhu, Meng; Zhou, Wen; Sun, Ryan; Bossé, Yohan; Song, Zhuoyi; et al. (Nature genetics, 2022)
To identify new susceptibility loci to lung cancer among diverse populations, we performed cross-ancestry genome-wide association studies in European, East Asian and African populations and discovered five loci that have not been previously reported. We replicated 26 signals and identified 10 new lead associations from previously reported loci. Rare-variant associations tended to be specific to populations, but even common-variant associations influencing smoking behavior, such as those with CHRNA5 and CYP2A6 , showed population specificity. Fine-mapping and expression quantitative trait locus colocalization nominated several candidate variants and susceptibility genes such as IRF4 and FUBP1 . DNA damage assays of prioritized genes in lung fibroblasts indicated that a subset of these genes, including the pleiotropic gene IRF4 , potentially exert effects by promoting endogenous DNA damage. A cross-ancestry genome-wide association meta-analysis of lung cancer including 61,047 cases and 947,237 controls identifies five new cross-ancestry susceptibility loci and highlights ancestry-specific effects of common and rare variants on lung cancer risk.